2016
DOI: 10.1515/bot-2015-0072
|View full text |Cite
|
Sign up to set email alerts
|

No sex-related dispersal limitation in a dioecious, oceanic long-distance traveller: the bull kelp Durvillaea antarctica

Abstract: Dispersal of dioecious floating seaweeds could be limited due to biological constraints. This study examined for benthic and floating populations (stranded individuals) of the rafting kelp Durvillaea antarctica whether male and female individuals cohabit within one holdfast. As a previous study had indicated colour differences between sexes, we also examined whether these colour differences are consistent and possibly related to pigment and phlorotannin concentrations. Our large-scale survey of rafted holdfast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…At mid latitudes (Concepción), M. pyrifera showed high reproductive activity in both seasons indicating their perennial strategies and high potential for rafting dispersal under moderate environmental conditions. In contrast, Durvillaea antarctica showed a strong seasonal (fall-winter) reproductive pattern in benthic (Santelices et al, 1980;Collantes et al, 2002) as well as in floating conditions Lizée-Prynne et al, 2016) along the SE Pacific. The consistently seasonal reproductive phenology of D. antarctica (Santelices et al, 1980;Collantes et al, 2002;Tala et al, 2013), confirmed herein for all three study sites, suggests that successful gamete dispersal is restricted to the cold season throughout its distributional range.…”
Section: Seasonal Effects On Floating Kelpsmentioning
confidence: 78%
“…At mid latitudes (Concepción), M. pyrifera showed high reproductive activity in both seasons indicating their perennial strategies and high potential for rafting dispersal under moderate environmental conditions. In contrast, Durvillaea antarctica showed a strong seasonal (fall-winter) reproductive pattern in benthic (Santelices et al, 1980;Collantes et al, 2002) as well as in floating conditions Lizée-Prynne et al, 2016) along the SE Pacific. The consistently seasonal reproductive phenology of D. antarctica (Santelices et al, 1980;Collantes et al, 2002;Tala et al, 2013), confirmed herein for all three study sites, suggests that successful gamete dispersal is restricted to the cold season throughout its distributional range.…”
Section: Seasonal Effects On Floating Kelpsmentioning
confidence: 78%
“…Lizée‐Prynne et al. () showed for stranded and benthic holdfasts of D. antarctica that between 5% and 17% of all plants contain both sexes in reproductive stage, although only 50% tended to have multiple stipes. Consequently, the probability of successful rafting dispersal is lower in areas with small plants, such as the MED.…”
Section: Discussionmentioning
confidence: 99%
“…Given the purpose of the study and to simplify subsequent analyses, herein we only distinguished two maturity stages of tissues, namely “vegetative” and “reproductive” (see also Lizée‐Prynne et al. ): Vegetative: absence of cellular differentiation or initial differentiation of immature conceptacle between the subcortex and the medulla. In some cases, there may be newly formed conceptacles but, as the gametes are undeveloped and the sex is unidentifiable, these samples were considered as vegetative.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations